Highly-coherent second-harmonic generation in a chip-scale source - Xuanyi Liu; Hongyan Fu (Light: Science & Applications, 2024)
Abstract A highly efficient second-harmonic source is integrated into a silicon nitride microring resonator, unlocking the potential for advanced chip-scale devices such as miniaturized atomic clocks and fully integrated self-referenced microcombs.